Adding automatic evaluation to interactive virtual labs. Issue 7 (2nd October 2016) - Farias, Gonzalo; Muñoz de la Peña, David; Gómez-Estern, Fabio; De la Torre, Luis; Sánchez, Carlos; Dormido, Sebastián
Abstract : Automatic evaluation is a challenging field that has been addressed by the academic community in order to reduce the assessment workload. In this work we present a new element for the authoring tool Easy Java Simulations (EJS). This element, which is named automatic evaluation element (AEE), provides automatic evaluation to virtual and remote laboratories built with EJS by using the server application Goodle grading management system (GMS). The integration of both tools entitles a professor to create interactive virtual and remote laboratories and automatically evaluate the work of their students. As a test bed two case studies are presented; a non-linear controller design virtual laboratory used in an advanced control master course and a servomechanism virtual laboratory used in an undergraduate basic control course.